Development of a Deployable Reflector Antenna for the Synthetic Aperture Radar Satellite, Part 2: Manufacturing and Qualification of the Main Reflector Using a Honeycomb Sandwich Composite Structure - Dong-Geon Kim; Hyun-Guk Kim; Dong-Yeon Kim; Ryoon-Ho Do; Kyung-Rae Koo; Young-Joon Yu (Applied Sciences)
A deployable reflector antenna (DR-A) is a structure that can be stored in a large-diameter Synthetic Aperture Radar (SAR) antenna and be mounted onto a launch vehicle. Considering the performance of the launch vehicle, it is necessary to develop a lightweight, high-performance antenna structure. The solid-type deployable reflector antenna is composed of a number of unit main reflectors. To reduce the weight of the antenna, a lightweight main reflector must be developed. In this paper, following “Development of Deployable Reflector Antenna for the SAR Satellite (Part 1)”, the manufacturing and qualification of the main reflector using honeycomb sandwich composites are described. Four types of composite main reflectors were manufactured with variables in the manufacturing process. The manufacturing variables include the curing process of the structure, the application of an adhesive film between the sheet and the core, and the venting path inside of the sandwich core. After manufacturing the main reflector, we performed weight measurements, non-destructive testing (NDT), surface error measurement using a Coordinate Measurement Machine (CMM), and modal testing for each type of composite main reflector. Through the research and development process, we found that a perforated hole is necessary when excluding the adhesive film during bonding of an aramid core and a CFRP sheet, and a lightweight composite reflector could be developed through this process. We selected the main reflector with the best performance and developed a composite main reflector that can be applied to satellites.